2000
DOI: 10.1046/j.1464-410x.2000.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative incidence of detrusor instability and bacterial cystitis detected on the urodynamic‐test day

Abstract: Objective To determine whether patients with detrusor instability (DI) were more likely to have bacterial cystitis or signi®cant bacteriuria on the urodynamictest day than were women with a stable bladder. Patients and methods A catheter specimen of urine was cultured (overnight in air) from 862 consecutive women at the time of urodynamic testing. The upper urinary tract was imaged, with cystoscopy when indicated, to exclude upper tract lesions or malignancy. The percentage of patients with pure idiopathic DI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
3
18
0
2
Order By: Relevance
“…Although some authors [6,7] have studied the relationship between bacterial cystitis and urodynamically proven IDC, these studies were performed in an era during which the definition of involuntary detrusor (detrusor instability) was not well established or when it was only applicable to cases with high-amplitude detrusor contractions (>15 cm H 2 O); therefore, many cases that would now be diagnosed with detrusor overactivity or OAB were overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some authors [6,7] have studied the relationship between bacterial cystitis and urodynamically proven IDC, these studies were performed in an era during which the definition of involuntary detrusor (detrusor instability) was not well established or when it was only applicable to cases with high-amplitude detrusor contractions (>15 cm H 2 O); therefore, many cases that would now be diagnosed with detrusor overactivity or OAB were overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…In the same manner, nonbacterial urinary tract symptoms may be related to the troublesome symptoms that are not due to any endotoxin but are only due to dysfunctional voiding that presents as a cystitis-like syndrome [7]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we previously mentioned, the effects of α-Defensin 1 on the contractility of vascular smooth muscle are yet unclear, being a subject of debate. There was a significant association between idiopathic instability of the detrusor muscle and bacterial cystitis and also reported that, in some women with an unstable bladder, urinary infection may enhance contractility of the detrusor muscle [16].…”
Section: Discussionmentioning
confidence: 89%